Rozważania na temat rodziny w publikacjach Józefa Becka. Komunikat z badań - Suska, Agnieszka (Karkonoska Państwowa Szkoła Wyższa, 2011)
Issues connected with the families of the Second Republic are discussed in the article. The problem is addressed form the perspective of the writings of Józef Beck, a prominent politician and respected local official. There is a rich legacy of the opinions and aspirations of Józef Beck contained in newspapers, brochures and books. Issues concerning family are often addressed in these writings on diverse subjects. The views can be divided into two groups, with those in the first one directly addressing family issues and those in the second one implying indirect relation to family issues. The picture of the family to be found in the publications of Józef Alojzy Beck is a collection of issues and problems crucial to the family which may be greatly influenced by local government. Initiative in the areas of public healthcare, school education and combating illiteracy are but a few of the problems that needto be solved in order to improve the quality of life of village families.
Keywords: Józef Beck; family; local government; child; education